Employment Potential of Forest-based Industries - Chatterjee, N. (Indian Forester, 1978)
Among the objectives of the present economic and industrial policies that tend to attract attention are the twin goals of employment creation and, through it, the improvement of income distribution in the society. Although foresters have long recognized the role that forest-based industries could play in this respect, no comparative assessment of product-wise potential of fulfilling these objectives appear readily available at present. In this paper a "micro-study method" for estimating the direct and indirect, total labour and other factor generating potential of industrial (or other) activities is thus described and applied to nine forest-based commodities. The ex-post study reveals that the safety match industry appears to posses the greatest employment creating potential per unit value of output at producer's price, and particleboard the least. The remaining forest-based industries are also ranked on difFerent criteria adopted for the purpose.